2014
DOI: 10.1051/mbcb/2013106
|View full text |Cite
|
Sign up to set email alerts
|

Paralysie faciale périphérique et soins dentaires : lien ou coïncidence, pour quelle prise en charge ?

Abstract: Résumé -Introduction : L'atteinte du nerf facial est angoissante pour le patient du fait de la déformation faciale qu'elle entraîne et pour le praticien qui se sent impuissant. La survenue d'une paralysie faciale périphérique, suite à des soins dentaires, est rare. Lorsqu'elle survient, aucune notion de traumatisme ou d'étiologie iatrogène ne peut être mise en cause de manière formelle. Observation : Le cas d'une patiente atteinte d'une paralysie faciale périphérique de grade IV selon la classification de Hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This case suggests that Bell's palsy may be associated with COVID-19 and this infection may be a potential cause of facial paralysis. From a pathophysiological point of view, it has been suggested that peripheral facial paresis may result from facial nerve reactivity in HSV-1 infection and that, as such, episodes of peripheral facial paresis may be caused by stress (or trauma, for example after dental treatment) [15].…”
Section: Discussionmentioning
confidence: 99%
“…This case suggests that Bell's palsy may be associated with COVID-19 and this infection may be a potential cause of facial paralysis. From a pathophysiological point of view, it has been suggested that peripheral facial paresis may result from facial nerve reactivity in HSV-1 infection and that, as such, episodes of peripheral facial paresis may be caused by stress (or trauma, for example after dental treatment) [15].…”
Section: Discussionmentioning
confidence: 99%
“…From a pathophysiological standpoint, it has been suggested that facial nerve paralysis could result from the reactivation of herpes simplex virus type 1 (HSV-1) infection within the facial nerve [2,3,11] and that as such, episodes of facial paralysis could be provoked by stress (or trauma, e.g. following dental treatment [11]), in analogy to herpes labialis [4]. The present case gives credence to such theory, as idiopathic facial paralysis occurred concurrently with a major anxiety episode secondary to COVID-19-related lockdown and subsequent socio-economical repercussions.…”
Section: Commentarymentioning
confidence: 99%